Flock With God, Ally With Money: Ziarah Wali As Generator of Local Economy - M Rizal Abdi (Postgraduate State Islamic Institute (IAIN) Metro, 2017)
Religion and economy have been influential forces in shaping world throughout history andpilgrimage is the apparent evidence where both forces are working side by side.In Indonesia, ziarah wali has a history of being an economic generator in the areas pilgrims visited. On many cases, the local government took over the site in order to manage it as better tourism site. As the consequences, the pilgrimage sites become more opens to all citizens regardless their cultural or religious backgroundas well as generate the activity around the site into marketplaces. However, many scholars frame the phenomena as devaluating the sacredness of the site and perceive the economic activity around the site is merely mundane practices. Reflecting from those issues, this researchexamines the economic activities around mausoleum of Sunan Bayat in two ways. First, it demonstrates how the existence of pilgrimage in Tembayat generates the local economy around the site and become village prime source of income. Second, it also scrutinizes how the economic practitioners in Tembayat site regard their economic practice as manifestation of barakah from waliyullah. By doing so, they negotiate with harsh competition among the tradersand sustain their economic activity. The findings contribute on the scholarship of Islam and local economy by showing how religious practice generate economic activities and reciprocally how economic activities become the means of religious practice at the same time.